Coating material set, coating film forming method, and laminate
Patent Information
- Application Number
- JP2021086838
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-25
- Filing Date
- 2021-05-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-05-24
AI Technical Summary
Conventional decorative coatings using scaly particles result in uneven patterns and colors due to variations in particle density, leading to aesthetic issues.
A coating material set comprising a first coating material forming a base layer and a second coating material containing colored particles, with a controlled color difference (ΔE) between 0.5-15, ensuring a uniform color and aesthetic appearance.
The solution achieves a coating with a uniform color and excellent aesthetics by using a laminated structure with controlled color variation, enhancing the visual appeal and pattern balance.
Abstract
Description
Technical Field
[0001] The present invention relates to a novel coating material set and the like.
Background Art
[0002] Conventionally, there has been known a decorative finishing method for imparting a natural stone-like aesthetic appearance to buildings and civil engineering structures. In recent years, there has been an increasing number of cases where a decorative finish having design properties such as various colors peculiar to natural stone is desired. As such a method, for example, Patent Document 1 describes a method of applying a resin mixed with colored mica (scaly particles) onto a base material. When scaly particles are used in this way, it is also advantageous for thinning and lightening the formed film.
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0004] However, when a coating material containing scaly particles is applied as in Patent Document 1 above, there is a risk of unevenness in the formed pattern and color tone due to partial weight, dense parts, or sparse parts between the scaly particles.
[0005] The present invention has been made in view of such points, and an object thereof is to provide a coating material capable of forming a film excellent in aesthetic appearance having a pattern derived from scaly particles and exhibiting a uniform color tone by a simple method.
Means for Solving the Problems
[0006] As a result of intensive studies to solve the above problems, the present inventor has conceived of a coating material set composed of at least two specific coating materials and the like, and has completed the present invention.
[0007] That is, the present invention has the following features. 1. A coating material set for forming a laminated film, The above coating material set consists of at least a first coating material and a second coating material. The above-mentioned first coating material is a coating material that forms the base layer, The above-mentioned second coating material contains resin components and colored particles, and is a coating material that forms a design layer. The above colored particles include base-colored flake-like particles. A coating material set characterized in that the color difference (△E) between the above-mentioned base layer and the above-mentioned base-colored flake-like particles is 0.5 to 15. 2. A method for forming a coating by sequentially applying a first coating material and a second coating material to a substrate, The above-mentioned first coating material is a coating material that forms the base layer, The above-mentioned second coating material contains resin components and colored particles, and is a coating material that forms a design layer. The above colored particles include base-colored flake-like particles. A method for forming a coating characterized in that the color difference (△E) between the above-mentioned base layer and the above-mentioned base-colored flake-like particles is 0.5 to 15. 3. A laminate comprising a base layer and a design layer sequentially laminated on a substrate, The above base layer is formed by the first coating material, The above design layer is formed from a second coating material containing resin components and colored particles. The above colored particles include base-colored flake-like particles. A laminate characterized in that the color difference (△E) between the above-mentioned base layer and the above-mentioned base-colored flake-like particles is 0.5 to 15. [Effects of the Invention]
[0008] According to the present invention, it is possible to form a coating with excellent aesthetic appeal that has a pattern derived from flake-like particles and exhibits a uniform color. [Modes for carrying out the invention]
[0009] The following describes embodiments for carrying out the present invention.
[0010] The present invention relates to a coating material set for forming a laminated film, and is characterized by comprising at least a first coating material and a second coating material.
[0011] <First covering material> The first coating material of the present invention is a coating material that forms a base layer. The first coating material preferably contains at least a resin component (A) and a coloring pigment (B). The resin component (A) (hereinafter also referred to as "component (A)") is not particularly limited, but one or more selected from water-soluble resins and water-dispersible resins (resin emulsions) are preferred. Examples of resin types include vinyl acetate resin, polyester resin, alkyd resin, vinyl chloride resin, epoxy resin, acrylic resin, urethane resin, acrylic silicone resin, fluororesin, etc., or composites thereof. These can be used one or more. In the present invention, acrylic resin and acrylic silicone resin are preferred. Furthermore, these components (A) may have crosslinking reactivity. When a component (A) with crosslinking reactivity is used, the water resistance, weather resistance, chemical resistance, etc. of the coating can be improved.
[0012] In the present invention, acrylic resin is particularly preferred as component (A). Acrylic resin is a resin in which alkyl (meth)acrylate is the main component of the resin skeleton, and other monomers are copolymerized as needed. In this invention, alkyl acrylate and alkyl methacrylate are collectively referred to as alkyl (meth)acrylate. Furthermore, monomer is a general term for compounds having polymerizable unsaturated double bonds.
[0013] Examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, cyclohexyl (meth)acrylate, etc., and one or more of these can be used.
[0014] Other specific examples of monomers include, for example, Aromatic monomers such as styrene, 2-methylstyrene, vinyltoluene, t-butylstyrene, chlorostyrene, vinylanisole, vinylnaphthalene, divinylbenzene, phenyl(meth)acrylate, and benzyl(meth)acrylate; Nitrile group-containing monomers such as (meth)acrylonitrile, vinylidene cyanide, and α-cyanoethyl (meth)acrylate; Amide group-containing monomers such as maleic acid amide, (meth)acrylamide, N-monoalkyl(meth)acrylamide, N,N-dialkyl(meth)acrylamide, 2-(dimethylamino)ethyl (methacrylate), N-[3-(dimethylamino)propyl](meth)acrylamide, and vinylamide; Carbonyl group-containing monomers such as acrolein, diacetone (meth)acrylamide, vinyl methyl ketone, vinyl ethyl ketone, and vinyl butyl ketone;
[0015] Carboxyl group-containing monomers such as (meth)acrylic acid, crotonic acid, maleic acid, itaconic acid, fumaric acid, isocrotonic acid, and salicylic acid; Amino group-containing monomers such as aminomethyl acrylate, aminoethyl acrylate, aminopropyl (meth)acrylate, amino-n-butyl (meth)acrylate, butylvinylbenzylamine, vinylphenylamine, p-aminostyrene, N-methylaminoethyl (meth)acrylate, and Nt-butylaminoethyl (meth)acrylate; Epoxy group-containing monomers such as glycidyl (meth)acrylate, diglycidyl fumarate, 3,4-epoxycyclohexyl (meth)acrylate, 3,4-epoxyvinylcyclohexane, allyl glycidyl ether, ε-caprolactone-modified glycidyl (meth)acrylate, and β-methylglycidyl (meth)acrylate; Hydroxyl group-containing monomers such as hydroxypropyl (meth)acrylate, ethylene glycol mono(meth)acrylate, and glycerol mono(meth)acrylate; vinylidene halogenated monomers such as vinylidene fluoride; Alkoxysilyl group-containing monomers such as vinyltrimethoxysilane, vinyltriethoxysilane, γ-(meth)acryloyloxypropyltrimethoxysilane, γ-(meth)acryloyloxypropyltriethoxysilane, and γ-(meth)acryloyloxypropylmethyldimethoxysilane; Examples include ethylene, propylene, isoprene, butadiene, vinyl ether, vinyl ketone, etc. These can be used individually or in combination of two or more.
[0016] When the above-mentioned alkoxysilyl group-containing monomer is used as another monomer, an acrylic silicone resin can be obtained.
[0017] Component (A) can be produced by emulsion polymerization of a group of monomers obtained by appropriately mixing the above monomers. Any known polymerization method may be used, and in addition to ordinary emulsion polymerization, soap-free emulsion polymerization, feed emulsion polymerization, seed emulsion polymerization, etc., can also be used. During polymerization, emulsifiers, initiators, dispersants, polymerization inhibitors, polymerization inhibitors, buffers, chain transfer agents, etc., can be used.
[0018] Various surfactants suitable for emulsion polymerization can be used as emulsifiers, and these may be reactive types (reactive surfactants) having polymerizable unsaturated double bonds. Preferably, anionic surfactants and nonionic surfactants can be used as emulsifiers, either alone or in combination.
[0019] The glass transition temperature (hereinafter simply referred to as "Tg") of component (A) above is preferably set to -50°C to 50°C. If Tg is within this range, the effects of the present invention can be stably obtained. In this invention, Tg is a value obtained by Fox's formula. Furthermore, the average particle diameter of component (A) above is preferably 300 nm or less (more preferably 20 to 200 nm). If the average particle diameter is within this range, the water resistance, weather resistance, chemical resistance, etc. of the coating can be improved. The average particle diameter referred to here is a value measured by dynamic light scattering.
[0020] The coloring pigment (B) (hereinafter also referred to as "component (B)") is a component that imparts color, opacity, etc., to the first coating material. Examples of component (B) include inorganic chromatic pigments such as ferric oxide (red iron oxide), yellow iron oxide, ultramarine, and cobalt green; organic chromatic pigments such as azo, naphthol, pyrazolone, anthraquinone, perylene, quinacridone, disazo, isoindolinone, benzimidazole, phthalocyanine, and quinophthalone; black pigments such as carbon black, iron-manganese composite oxide, iron-copper-manganese composite oxide, iron-chromium-cobalt composite oxide, copper-chromium composite oxide, copper-manganese-chromium composite oxide, and black iron oxide; white pigments such as titanium dioxide, zinc oxide, and alumina; and other luminous pigments (pearl pigments, aluminum pigments, metallic pigments, etc.), phosphorescent pigments, and fluorescent pigments. These can be used individually or in combination of two or more. The average particle size of component (B) is preferably 1 μm or less, more preferably 0.01 to 0.9 μm. The average particle size of the coloring pigment is measured by a laser diffraction particle size distribution analyzer. In this invention, "α to β" is synonymous with "α or more and β or less".
[0021] Component (B) is preferably present in an amount of 3 to 300 parts by weight (more preferably 5 to 250 parts by weight) per 100 parts by weight of the solid content of component (A). With component (B) in this ratio, the first coating material (base layer) can be colored to the desired color, thereby improving aesthetics and other aspects.
[0022] Furthermore, the first coating material preferably contains powder components other than coloring pigments (hereinafter also referred to as "(C) component"). Examples of such (C) component include extender pigments such as heavy calcium carbonate, light calcium carbonate, kaolin, clay, pottery clay, china clay, diatomaceous earth, hydrated fine silica, talc, mica, barite powder, barium sulfate, precipitated barium sulfate, barium carbonate, magnesium carbonate, silica powder, and aluminum hydroxide; and powders and granules such as silica particles, crushed rock, glass, ceramics, seashells, sintered bodies, concrete, mortar, plastics, rubber, etc. These may be colored. These can be used individually or in combination of two or more.
[0023] Furthermore, component (C) preferably has a particle size of 1 to 1000 μm (more preferably 5 to 850 μm, and even more preferably 10 to 600 μm). Also, for example, if powder (C1) with a particle size of 53 to 300 μm is included in the total amount of component (C) at a rate of preferably 40% by weight or more (more preferably 45% by weight or more, and even more preferably 50% by weight or more), a coating with even better aesthetics can be formed. The upper limit is preferably 100% by weight or less (more preferably 95% by weight or less, and even more preferably 90% by weight or less). Such embodiments are even more preferable in terms of improving the effects of the present invention. The particle size of component (C) can be measured if it is greater than 20 μm by sieving using a metal mesh sieve as specified in JIS Z8801-1:2000. If it is 20 μm or less, it can be measured using a laser diffraction particle size distribution analyzer.
[0024] Component (C) is preferably present in an amount of 10 to 600 parts by weight (more preferably 30 to 500 parts by weight, and even more preferably 50 to 400 parts by weight) per 100 parts by weight of solid content of component (A). By including component (C) in this ratio, a base layer with even greater aesthetic appeal can be formed. Furthermore, by including granular material (C1) with a particle size of 53 to 300 μm, it is possible to form fine irregularities on the surface of the base layer originating from component (C1). This makes it easier to perceive a uniform color, further enhancing the effects of the present invention. Moreover, it is possible to suppress the roughness caused by the bouncing of the edges of the flaky particles in the design layer.
[0025] The first coating material can be manufactured by uniformly mixing the above components by known methods, but other components that can be commonly used in coating materials may also be mixed in as needed. Examples of such components include pigment dispersants, emulsifiers, thickeners, film-forming aids, leveling agents, coupling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, drying adjusters, preservatives, antifungal agents, antialgal agents, antibacterial agents, defoaming agents, adsorbents, deodorizers, fibers, ultraviolet absorbers, light stabilizers, antioxidants, catalysts, crosslinking agents, and the like.
[0026] <Second covering material> The second coating material of the present invention is a coating material that forms a design layer, and is characterized by containing a resin component (A) and colored particles (D).
[0027] The resin component (A) in the second coating material is not particularly limited, and any resin selected from the same resins as component (A) of the first coating material can be used. These can be used individually or in combination of two or more types.
[0028] The colored particles (D) (hereinafter referred to as "component (D)") impart design aesthetics. The present invention is characterized in that component (D) includes base color flaky particles (d1). This makes it possible to obtain a design layer that has a base pattern (a pattern derived from the flaky particles) formed by the base color flaky particles (d1) and exhibits a uniform and consistent color with minimal color unevenness.
[0029] In the present invention, the base color flake particles (d1) (hereinafter referred to as "component (d1)") are flake particles of one color (one type) that exhibit the base color of the design layer, and are the main component (the component with the highest content) included in component (D). Examples of component (d1) include flake-shaped substrate particles that have been colored. Specifically, examples of substrate particles include mica, sericite, clay, talc, plate-like kaolin, barium sulfate flakes, glass flakes, alumina flakes, shell fragments, metal fragments and other inorganic fragments, or rubber fragments, plastic fragments, wood fragments, etc. The coloring treatment is not particularly limited, but examples include coating (or adsorbing) the substrate particles with a coloring agent containing pigments or dyes, or applying a firing treatment to the substrate particles. In the present invention, it is preferable to use mica (colored mica) that has been coated with a coloring agent. By including such (d1) component as the main component, it is advantageous not only for aesthetic appeal but also for thinning the design layer and reducing weight.
[0030] The "flak-like particles" in this invention are not particularly limited as long as their shape is flake-like (thin flake-like), but it is preferable that the particles have an aspect ratio (ratio of "short diameter / thickness") of 1.5 to 2000 (more preferably 2 to 500, and even more preferably 3 to 100). It is also preferable that the ratio of the short diameter to the long diameter (short diameter / long diameter) is 0.3 to 1 (more preferably 0.4 to 1, and even more preferably 0.5 to 1). When the size of the flake-like particles satisfies the above range, their shape is easily visible and suitable as a design. Furthermore, it is possible to form a design layer that is excellent in terms of thinning the design layer, reducing its weight, etc. The "short diameter," "long diameter," and "thickness" referred to herein are calculated by placing the flake-like particles stably on a horizontal surface and observing them from above with a microscope, with the shortest part length being the "short diameter," the longest part length being the "long diameter," and the maximum height from the bottom surface being the "thickness," and these values are measured with a micrometer.
[0031] In the present invention, it is characterized in that the base layer formed by the above first coating material and the color difference (ΔE) of the component (d1) is 0.5 to 15 (preferably 1.0 to 10, more preferably 1.5 to 8). In such a case, the hues of the base layer and the component (d1) are harmonious, and a homogeneous hue can be easily visually recognized as the base color (base color), and a laminated film excellent in aesthetics with little color unevenness and a sense of unity can be obtained. In particular, when the color difference (ΔE) satisfies the above range, even if the thickness (coating amount) of the design layer is partially uneven, a laminated film excellent in aesthetics with little color unevenness can be obtained.
[0032] On the other hand, when the color difference (ΔE) is less than 0.5, unevenness in color tone is likely to occur. The mechanism of this action is not limited, but the design layer formed by the second coating material exhibits a design by the base color scaly particles (d1), and depending on the overlapping condition, the viewing direction, and the environment (light irradiation condition), subtle changes may occur. When the base layer and the design layer with a color difference (ΔE) less than 0.5 are laminated, it is considered that color unevenness is likely to be visually recognized due to the characteristics of such scaly particles. Further, when the color difference (ΔE) exceeds 15, the hues of the base layer and the design layer are unlikely to be harmonious, and there is a risk of inferior designability. In the present invention, it is preferable to set the color difference between the base layer and the component (d1) within the above range based on the color of the component (d1).
[0033] The above color difference (ΔE) is a value measured using a color difference meter, and can be calculated by the following formula from the respective L* values, a* values, and b* values. <Formula> ΔE = {(L *1 - L *2 ) 2 + (a *1 - a *2 ) 2 + (b *1 - b *2 ) 2} 0.5 In the formula, L *1 , a *1 , b *1 are respectively the L * , a * , b * . L *2 a *2 , b *2 These are the L components of (d1), respectively. * a * , b * . The L*, a*, and b* values of the base layer described above can be calculated from the L*, a*, and b* values (average values from three or more measurement points) of the film when the first coating material is applied to standard white paper using a film applicator with a 2 mm gap, the coated surface is placed horizontally, and dried for 48 hours under standard conditions (temperature 23°C, relative humidity 50%; the same applies hereafter). Furthermore, the L*, a*, and b* of component (d1) can be calculated by placing component (d1) on a glass plate until the glass surface is obscured, and then measuring the surface covered with a colorless, transparent PE film.
[0034] In the present invention, as component (D), in addition to component (d1) above, a similar color (approximate color) flake-like particles (hereinafter referred to as component (d2)) of component (d1) may be included. Component (d2) is a component that, together with component (d1), constitutes the base color of the design layer. Such a component (d2) is a color other than that exhibited by component (d1), and it is preferable that the color difference (△E) from component (d1) is less than 2.5 (preferably greater than 0 and 2.4 or less). The same components as those used for component (d1) above can be used as such a component (d2). Furthermore, it is also possible to include two or more colors as component (d2).
[0035] The color difference (△E) of the above (d1) and (d2) components is a value measured using a colorimeter and can be calculated from the respective L*, a*, and b* values using the following formula. <Formula>△E={(L *3 -L *2 ) 2 +(a *3 -a *2 ) 2 +(b *3 -b *2 ) 2} 0.5 During the ceremony, L *2 a *2 , b *2 These are the L components of (d1), respectively. * a * , b * . L *3 a *3 , b *3 These are the L components of (d2), respectively. * a * , b * . Furthermore, the L*, a*, and b* values of components (d1) and (d2) can be calculated by placing component (D) on a glass plate until the glass surface is obscured, and then measuring the surface covered with a colorless, transparent PE film.
[0036] In the present invention, the (D) component may further include accent particles (d3) (hereinafter also referred to as the (d3) component). Accent particles are components that are scattered in the base color pattern obtained by the above-mentioned (d1) component (and (d2) component) and impart an accent pattern. In the present invention, the (d3) component may include at least one particle of a different type and / or color from the above-mentioned (d1) component. This makes it possible to impart an aesthetically pleasing design with an accent pattern. Examples of such (d3) components include aggregates, lustrous pigments, etc., which are particles of a different type from the (d1) component, or flake-like particles (accent-colored flake-like particles) that have a different hue from the (d1) component. These can be used one or more types.
[0037] When aggregate is included as component (d3), granular accent patterns can be added to the flat pattern formed by component (d1). For example, organic aggregate or inorganic aggregate can be used as aggregate, and transparent (translucent) aggregate or colored aggregate can be used. Examples of such aggregates include crushed natural stone, ceramic powder, metal granules, silica sand, feldspar, silica, crushed stone, glass beads, rubber granules, resin beads, etc., and these may be colored. Aggregates of the same hue as component (d1) can also be used. The particle size of the colored aggregate is 0.01 mm to 5 mm (more preferably 0.03 mm to 4.5 mm). If a luminous pigment is included as component (d3), a sense of brightness can be imparted to the pattern formed by component (d1). Examples of luminous pigments include pearl pigments, aluminum pigments, and metallic pigments. The particle size of the luminous pigment is preferably 0.5 to 100 μm (more preferably 1 to 80 μm). The particle size of the aggregate can be measured by sieving using a metal mesh sieve as specified in JIS Z8801-1:2000. The particle size of the luminous pigment can be measured using a laser diffraction particle size distribution analyzer.
[0038] In the present invention, it is preferable that the (d3) component includes accent color flake-like particles (d31) (hereinafter also referred to as "(d31) component"). The (d31) component exhibits an accent color in the design layer and is scattered within the base color pattern obtained by the (d1) component (and (d2) component) to provide an accent pattern. The (d31) component can be any color other than that exhibited by the (d1) component (and (d2) component), and the same as the (d1) component can be used. In addition, an uncolored (d31) component can be used, for example, the flake-like base particles of the (d1) component can be used without treatment. Furthermore, it is also possible to include two or more colors (preferably 2 to 6 colors) as the (d31) component. This makes it possible to provide a more diverse range of colors and other design features to the laminate (laminated film) formed by laminating the base layer and the design layer. In this invention, "different color" means a color that is distinguishable by visual inspection, but it is preferable that the color difference △E with component (d1) is 2.5 or more (more preferably 3 or more).
[0039] The color difference (△E) of the above (d1) component and (d31) component is a value measured using a colorimeter and can be calculated from the respective L*, a*, and b* values using the following formula. <Formula>△E={(L *4 -L *2 ) 2 +(a *4 -a *2 ) 2 +(b *4 -b *2 ) 2} 0.5 During the ceremony, L *2 a *2 , b *2 These are the L components of (d1), respectively. * a * , b * . L *4 a *4 , b *4 These are the L components of (d31), respectively. * a * , b * . Furthermore, the L*, a*, and b* values of components (d1) and (d31) can be calculated by placing component (D) on a glass plate until the glass surface is obscured, and then measuring the surface covered with a colorless, transparent PE film.
[0040] The (D) component of the present invention is preferably (D') flake-like particles (hereinafter also referred to as "(D') component"). The (D') component preferably includes base-colored flake-like particles (d1), similar-colored flake-like particles (d2) and / or accent-colored flake-like particles (d31) as needed. Furthermore, the (D') component preferably includes large particles (L) with a short diameter of more than 2 mm (hereinafter referred to as "large particles (L)"), medium particles (M) with a short diameter of more than 0.7 mm and less than or equal to 2 mm (hereinafter referred to as "medium particles (M)"), and small particles (S) with a short diameter of 0.7 mm or less (hereinafter referred to as "small particles (S)"). By using flake-like particles of different sizes in combination in this way, uneven distribution of flake-like particles is less likely to occur, resulting in a well-balanced (arranged) pattern and a highly aesthetically pleasing coating with less roughness. It is also possible to impart natural stone-like colors and large patterns.
[0041] Specifically, the large particles (L) are mainly suitable for effectively imparting large patterns to the formed film, and in the present invention, it is preferable to include large particles (L) as component (d31). The medium particles (M) are mainly suitable for forming the base pattern (base color) of the formed film, and in the present invention, it is preferable to include medium particles (M) as components (d1) and (d2). Furthermore, the small particles (S) are suitable for imparting small patterns to the formed film and for imparting opacity to the formed film, and in the present invention, it is preferable to include small particles (S) as one or more selected from components (d1), (d2), and (d31) (preferably one or more selected from components (d1) and (d2)).
[0042] In the present invention, it is preferable to use the above-mentioned large particles (L), medium particles (M), and small particles (S) in a specific weight ratio, and it is preferable that the weight ratio of the above-mentioned medium particles (M) and small particles (S) to the above-mentioned large particles (L) [(M) + (S)] / (L) is 1 or more and 50 or less (more preferably 3 or more and 40 or less, and even more preferably 5 or more and 30 or less). When this range is satisfied, the above-mentioned large particles (L) are less likely to be unevenly distributed, and a coating with excellent aesthetics can be formed in which the large pattern formed by the above-mentioned large particles (L) is well-balanced (arranged) within the base pattern formed by the above-mentioned medium particles (M) and small particles (S). Furthermore, the above-mentioned medium particles (M) and small particles (S) can suppress the upward curvature of the edges of the above-mentioned large particles (L), and a flat coating with less roughness can be formed. Furthermore, it is preferable that the weight ratio (M) / (S) of the medium particles (M) to the small particles (S) is 1 or more and 30 or less (more preferably 1.5 or more and 20 or less, and even more preferably 2 or more and 10 or less). When this range is met, the above effects can be further enhanced.
[0043] The mechanism by which such effects are achieved is not limited, but for example, medium-sized particles (M) and small particles (S), which are smaller than large particles (L), act as spacers for the large particles (L), contributing to their dispersibility. Similarly, small particles (S), which are smaller than medium-sized particles (M), act as spacers for the medium-sized particles (M), contributing to their dispersibility. As a result, it is presumed that the (D') component dispersed in the coating material allows the large particles (L), medium particles (M), and small particles (S) to maintain good dispersibility. In particular, in a coating material containing a relatively large amount of medium particles (M), it is presumed that the large particles (L) and small particles (S) are dispersed in a well-balanced manner within the medium particles (M). By applying such a coating material, it is presumed that the particles are less likely to become unevenly distributed, a coating with a well-balanced pattern is formed, and the bouncing of particle edges can be sufficiently suppressed.
[0044] In this invention, the minor axis of component (D') refers to the length of the shortest part when the flake-like particles are stably placed on a horizontal surface, as described above. The large particles (L), medium particles (M), and small particles (S) can be classified by sieving using a metal mesh sieve (standard sieve) as specified in JIS Z8801-1:2000. In this case, if the mesh opening of the standard sieve is "a", then the length of its diagonal "L = √2a" can be considered to correspond to the minor axis. Specifically, 100g of component (D') is weighed and sieved for 10 minutes using the test method (manual sieving) in accordance with JIS K 0069. • Those that do not pass through a 12-mesh sieve (a=1.4mm, L=2.0mm) are classified as large particles (L). - Grains that pass through a 12-mesh sieve (a=1.4mm, L=2.0mm) but not a 30-mesh sieve (a=0.5mm, L=0.7mm) are classified as medium particles (M). • Small particles (S) are those that pass through a 30-mesh sieve (a=0.5mm, L=0.7mm). Let's assume that. The upper limit for large particles (L) is preferably those that pass through a 6.5 mesh sieve (a=2.8 mm, L=4.0 mm) (particles with a short diameter of 4 mm or less). On the other hand, the lower limit for small particles (S) is preferably those that do not pass through a 70 mesh sieve (a=0.21 mm, L=0.3 mm) (particles with a short diameter of more than 0.3 mm).
[0045] In the present invention, it is preferable that the (D) component is included in an amount of 5 to 200 parts by weight (more preferably 10 to 100 parts by weight, and even more preferably 15 to 80 parts by weight) per 100 parts by weight of the solid content of the (A) component. Furthermore, it is preferable that the content of component (d1) included as the main component in component (D) be 40 to 100% by weight (more preferably 45 to 98% by weight, and even more preferably 50 to 97% by weight) relative to the total amount of component (D). In this case, component (d1) can be sufficiently visible as the base color of the second coating material (design layer), and an aesthetically pleasing coating with a uniform color can be formed. Furthermore, the content of components other than component (d1) is 0 to 60% by weight (more preferably 2 to 55% by weight, and even more preferably 3 to 50% by weight) relative to the total amount of component (D). Of these, it is preferable that the content of component (d2) (total in the case of multiple colors) be 0 to 50% by weight (more preferably 0 to 40% by weight) relative to the total amount of component (D). The content of component (d3) (total in the case of multiple colors) is preferably 0 to 60% by weight (more preferably 1 to 50% by weight) relative to the total amount of component (D). However, in components (d2) and (d3), the content of one color (one type) of flake-like particles (or aggregate, etc.) is less than the content of component (d1). In such a case, the accent pattern of component (d3) is well-balanced within the base color formed by components (d1) and (d2), and a coating with a design aesthetic such as a natural stone appearance can be obtained.
[0046] The second coating material of the present invention can be manufactured by uniformly mixing the above components by known methods, but other components that can be commonly used in coating materials may also be mixed in as needed. Examples of such components include coloring pigments, extender pigments, fibers, film-forming aids, thickeners, leveling agents, coupling agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, antialgal agents, antimicrobial agents, dispersants, defoaming agents, ultraviolet absorbers, light stabilizers, antioxidants, and water.
[0047] The coating material of the present invention is preferably an aqueous coating material. Furthermore, the pH of the coating material is preferably 7 to 12 (more preferably 7.5 to 11). Within this range, the effects of the present invention can be sufficiently enhanced. In addition, the non-volatile content of the coating material is preferably 10 to 80% by weight (more preferably 15 to 70% by weight). Within this range, it is possible to easily form designs such as the diverse colors characteristic of natural stone, and to obtain a coated film with less roughness and superior aesthetic appeal. The non-volatile content can be adjusted by adjusting the mixing ratio of each component.
[0048] <Film formation method> The present invention relates to a method for forming a coating, characterized by sequentially applying a first coating material and a second coating material to a substrate. For example, (1) A step of applying a first coating material to the substrate to form a base layer, (2) A step of applying a second coating material onto the base layer to form a design layer. Examples include coating formation methods that include the above.
[0049] The substrate is what constitutes the surface of buildings, civil engineering structures, etc. Examples of such substrates include concrete, mortar, siding boards, extruded boards, gypsum boards, slate boards, perlite boards, plywood, bricks, plastic sheets, metal sheets, glass, and porcelain tiles. These substrates may already have a coating formed on their surface or may have wallpaper attached to them.
[0050] In step (1) above, the substrate surface may be treated as necessary before applying the first coating material. Examples of surface treatments include filler treatment, putty treatment, surfacer treatment, and sealer treatment.
[0051] As the first coating material in (1) above, the first coating material described above is used. As for the application method of the first coating material, for example, spray application, roller application, trowel application, brush application, etc., can be used. Alternatively, a combination of these methods may be used.
[0052] The first coating material can be applied one or more times. The number of applications of the first coating material is preferably 1 to 2 times (more preferably 2 times). The amount of the first coating material applied is preferably 0.05 to 1 kg / m² per application. 2 (More preferably 0.1 to 0.8 kg / m 2 ) By applying the first coating material under these conditions, a base layer suitable for applying the second coating material can be formed, making it easier to obtain the effects of the present invention.
[0053] When applying the first coating material, the viscosity can be adjusted as appropriate by mixing in a diluent such as water. The dilution ratio is preferably 0 to 20% by weight. The viscosity of the first coating material to be applied is preferably 3 to 30 Pa·s (more preferably 4 to 20 Pa·s), and the thixotropy index is preferably 2 to 9 (more preferably 3 to 8). The viscosity and thixotropy index referred to here are values obtained using a BH-type viscometer as the measuring instrument (measurement temperature 23°C). Viscosity is the measured value when the rotation speed is 20 rpm. The thixotropy index is the value obtained by dividing the measured value at a rotation speed of 2 rpm by the measured value at a rotation speed of 20 rpm.
[0054] The first coating material may preferably be dried at room temperature (0 to 40°C). If the first coating material is applied multiple times, it is desirable to apply the subsequent first coating material after the film of the previous first coating material has dried.
[0055] In step (2) above, a second coating material is applied to the base layer formed in step (1) above to form a design layer. The second coating material used is the second coating material described above. As for the method of applying the second coating material, for example, spray coating, roller coating, trowel coating, brush coating, etc., can be used. In the present invention, spray coating and roller coating are preferred, and in particular, it is preferable to form the coating by spray coating using a spray gun. This makes it possible to uniformly apply the base color flake particles (d1) in the colored particles (D), and to obtain a formed coating with excellent aesthetics. Furthermore, in the case of flake particles (D'), unevenness of each flake particle ((d1), (d2), (d31)) is less likely to occur, the balance (arrangement) of the pattern is good, and a flat, aesthetically pleasing formed coating with little roughness can be easily formed.
[0056] The amount of the second coating material of the present invention applied is not particularly limited, but is preferably 0.05 to 1 kg / m² per application. 2 (More preferably 0.1 to 0.8 kg / m 2 Furthermore, the number of coats can be set by forming the desired design, but preferably it is 1 to 2 times (more preferably 2 times). In such cases, the effects of the present invention can be fully demonstrated.
[0057] When applying the second coating material, the viscosity can be adjusted as appropriate by mixing in a diluent such as water. The dilution ratio is preferably 0 to 20% by weight. The viscosity of the second coating material to be applied is preferably 1 to 50 Pa·s (more preferably 2 to 40 Pa·s), and the thixotropy index is preferably 3 or higher (even more preferably 3.5 to 15).
[0058] The second coating material may preferably be dried at room temperature (0 to 40°C). If the second coating material is applied multiple times, it is desirable to apply the second coating material after the film of the first coating material has dried.
[0059] The present invention is characterized in that the color difference (△E) between the base layer formed by step (1) above and the base-colored flake-like particles (d1) contained in the second coating material of step (2) above is 0.5 to 15 (preferably 1.0 to 12, more preferably 1.5 to 10). In this case, a coating with excellent aesthetics exhibiting a uniform color can be obtained. If the above color difference (△E) is less than 0.5, there is a risk of unevenness in the formed pattern and color. Also, if the above color difference (△E) exceeds 15, the hue of the base layer may stand out, resulting in poor design quality.
[0060] In the coating method of the present invention, a clear coating material may be applied to the outermost surface (above the design layer) to provide a clear layer, for purposes such as surface protection, improved weather resistance, and stain resistance, as long as it does not hinder the effects of the present invention. Such a clear layer may be colorless and transparent, or colored and transparent, and may be glossy or matte (including 70% gloss, 50% gloss, 30% gloss, etc.).
[0061] <Laminate> The laminate of the present invention is a laminate having a laminated coating obtained by sequentially laminating a base layer and a design layer on a substrate. The substrate used is the substrate described above. The base layer is formed by the first coating material described above, and the design layer is formed by the second coating material described above. This laminate (laminated coating) has the design layer laminated over the entire surface of the base layer, and the base layer can be seen through the gaps between the colored particles (D) that form the design layer. The laminate of the present invention is characterized in that the color difference (△E) between the base layer and the base colored flake-like particles (d1) contained in the design layer is 0.5 to 15 (preferably 1.0 to 12, more preferably 1.5 to 10). In such a case, a coating with excellent aesthetics exhibiting a uniform color can be obtained. If the above color difference (△E) is less than 0.5, there is a risk of unevenness in the formed pattern and color. Also, if the above color difference (△E) exceeds 15, the hue of the base layer may stand out, and the design may be inferior. [Examples]
[0062] The following examples illustrate the features of the present invention.
[0063] <Manufacturing of the first coating material> After preparing the white coating materials W1 to W3 described below, each coloring pigment (black, yellow, red, etc.) was added to adjust the color to the hues shown in Table 1, resulting in the first coating materials 1 to 7. (White covering material W1) White coating material 1 was prepared by mixing 200 parts by weight of acrylic silicone resin emulsion (solids content: 50% by weight, medium: water), 60 parts by weight of titanium dioxide, 200 parts by weight of powder components [silica powder with particle size 20 to 400 μm (content of particle size 53 to 300 μm: 75% by weight)], and additives (thickener, dispersant, defoamer, film-forming aid, etc.) by a conventional method. (White coating material W2) White coating material W2 was prepared in the same manner as white coating material 1, except that silica powder with a particle size of 20 to 400 μm (content of particles with a particle size of 53 to 300 μm: 45% by weight) was used as the powder component. (White covering material W3) White coating material W3 was prepared in the same manner as white coating material 1, except that calcium carbonate (particle size 20-38 μm) was used as the powder component.
[0064] [Table 1]
[0065] <Manufacturing of the second coating material> Based on the formulations shown in Table 2, acrylic resin emulsion (50% by weight solids, medium: water), colored particles (D), and additives (thickener, defoamer, film-forming aid, UV absorber, etc.) were mixed by conventional methods to produce second coating materials 1 to 14. Furthermore, the colored particles (D) were pre-mixed flake particles (D') based on the formulations shown in Table 3. The (D') components were then sieved, and [(M)+(S)] / (L) and (M) / (S) were calculated.
[0066] (D) Colored particles (D1): Light gray mica flakes [Short diameter: greater than 0.3 mm and less than or equal to 2 mm, Short diameter / Long diameter (average): 0.89, Short diameter / Thickness (average): 10.5, L value = 88.8, a value = -0.9, b value = 4.4] (D2): Light gray mica flakes [Short diameter: greater than 0.3 mm and less than or equal to 2 mm, Short diameter / Long diameter (average): 0.89, Short diameter / Thickness (average): 10.5, L value = 88.5, a value = -0.9, b value = 5.5] (D3): Light gray mica flakes [Short diameter: greater than 1 mm and less than or equal to 4 mm, Short diameter / Long diameter (average): 0.89, Short diameter / Thickness (average): 10.5, L value = 88.8, a value = -0.9, b value = 4.4] (D4): Yellow mica flakes [Short diameter: greater than 1 mm and less than or equal to 4 mm, Short diameter / Long diameter (average): 0.88, Short diameter / Thickness (average): 11.5, L value = 86.7, a value = 0.7, b value = 14.1] (D5): White mica flakes [Minor axis: greater than 1 mm and less than or equal to 4 mm, minor axis / major axis (average): 0.94, minor axis / thickness (average): 11.0, L value = 91.5, a value = 0.5, b value = 4.4] (D6): Yellow mica flakes [Short diameter: greater than 0.3 mm and less than or equal to 2 mm, Short diameter / Long diameter (average): 0.92, Short diameter / Thickness (average): 10.7, L value = 88.7, a value = 0.6, b value = 14.3] (D7): Gray mica flakes [Short diameter: greater than 0.3 mm and less than or equal to 2 mm, Short diameter / Long diameter (average): 0.87, Short diameter / Thickness (average): 15.5, L value = 69.3, a value = -0.7, b value = 0.2]
[0067] [Table 2]
[0068] [Table 3]
[0069] (Examples 1-9, Comparative Examples 1-3) Apply the first coating material at a rate of 0.3 kg / m² to the base material (slate board: 45 x 30 cm). 2The surface was spray-painted and dried at 23°C for 5 hours. Next, the second coating material was applied to half of the surface using a spray gun (nozzle diameter: 5.5 mm) at a rate of 0.5 kg / m². 2 For the first half, spray painting was done, and the remaining half was painted at a rate of 0.8 kg / m². 2 The material was spray-painted and dried and cured at 23°C for 24 hours to form a laminate. The combinations of the first and second coating materials are shown in Table 4.
[0070] <Rating> The following evaluations were conducted, and the results are shown in Table 4. • Aesthetics Laminates with varying amounts of coating were visually observed and their aesthetic appeal was evaluated. The evaluation criteria were as follows: "A" for materials exhibiting a uniform color regardless of the viewing direction (angle), and "D" for materials with color unevenness, with a four-level scale of A>B>C>D.
[0071] [Table 4]
[0072] In Examples 1 to 9, laminated coatings exhibiting a uniform color and excellent aesthetics were obtained. In particular, in Examples 1 to 2 and 5 to 7, laminated coatings exhibiting a uniform color regardless of the viewing direction (angle) were obtained, resulting in excellent aesthetics. On the other hand, in Comparative Examples 1 and 2, different colors were visible in areas with different coating amounts, resulting in color unevenness. Furthermore, in Comparative Example 3, the harmony of hue between the base layer and the design layer was poor.
[0073] (Examples 5, 10-20) A laminated coating was formed using the same method as in Example 1. The combinations of the first and second coating materials are shown in Table 5.
[0074] <Rating> The following evaluations were conducted, and the results are shown in Table 5. • Aesthetics Aesthetic appeal was evaluated in the same manner as described above. • Design Samples with minimal unevenness in the flake-like particles and a good balance of patterns were rated "AA," while those with inferior patterns were rated "D," resulting in a five-point scale: AA > A > B > C > D. • Texture (feel) Products with less roughness in the formed film were rated "AA," while those with a noticeable roughness were rated "D," and the evaluation was conducted on a five-point scale: AA > A > B > C > D.
[0075] [Table 5]
[0076] In Examples 5 and 10, a laminated coating with excellent aesthetics and a uniform color formed by component (d1) was obtained. In particular, Example 10 yielded a laminated coating with excellent design (balance of large, medium, and small particle patterns) and texture. Furthermore, Examples 11 to 20 yielded laminated coatings with excellent aesthetics, in which component (d3) was scattered within a patterned layer exhibiting a homogeneous color formed by component (d1). In particular, Examples 13 to 15 yielded laminated coatings with excellent design (balance of large, medium, and small particle patterns and balance of accent particles) and texture.
Claims
1. A coating material set for forming a laminate coating, comprising: the coating set includes at least a first coating material and a second coating material; the first coating material is a coating material that forms a base layer; the second coating material contains a resin component and colored particles and forms a design layer; the colored particles include base color scale-like particles, A coating material set, characterized in that the color difference (ΔE) between the base layer and the base-colored scaly particles is 0.5 to 15.
2. A coating formation method for sequentially applying a first coating material and a second coating material to a substrate, comprising: the first coating material is a coating material that forms a base layer; the second coating material contains a resin component and colored particles and forms a design layer; the colored particles include base color scale-like particles, A coating forming method characterized in that the color difference (ΔE) between the base layer and the base-colored scaly particles is 0.5 to 15.
3. A laminate obtained by laminating a base layer and a design layer in this order on a substrate, the base layer is formed of a first coating material, the design layer is formed from a second coating material containing a resin component and colored particles, the colored particles include base color scale-like particles, A laminate characterized in that the color difference (ΔE) between the base layer and the base-colored scaly particles is 0.5 to 15.